PENGARUH STRUKTUR KEPEMILIKAN, KONSERVATISME AKUNTANSI TERHADAP EARNING MANAGEMENT PADA PERUSAHAAN FOOD AND BEVERAGES YANG TERDAFTAR DI BURSA EFEK INDONESIA - B41108061, Ria Rinarti (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2013)
The purpose of this research is to examine the effect of institutional ownership and family ownership, conservatism on earning management practice in sample companies. Discretionary accrual is used to proxy earning management based on Modified Jones Model. This research is an econometric research based on panel data. 11 companies from food and beverages sector listed on Indonesia Stock Exchange (IDX) from 2009-2011 are selected as research samples by purposive sampling method. Total observations used in this research are 33 observations. Data are analyzed by multiple regressions method. According to test result, this research finds significant relationship between conservatism and earning management. Research can not find a significant relationship between family ownership and institutional ownership and earning management practice in sample companies. Keywords: earning management, family ownership, institutional ownership, conservatism